Statistical contrast analysis of hydrochemical parameters upstream the tidal influence in tinto and odiel rivers (SWS Spain) - De la Torre, M. L. (2014)
The Iberian Pyrite Belt (IPB), SW Spain, has been exploited since ancient times, and previous studies have compared different parameters in the Tinto and Odiel Rivers, the principal rivers that cross the IPB. We used classical statistics to draw contrasts between the two rivers. Samples were collected at two sites, one in the Tinto River, and the other in the Odiel, immediately upstream of tidal influence. Both rivers are strongly contaminated by acid mine drainage (AMD). However, the results suggest a distinctive, although somewhat parallel, geochemical behavior. The pattern of affinity between parameters differs because in addition to AMD, the Odiel River receives important contributions from non-contaminated catchments, while the Tinto River is the main receptor of drainage from the Rio Tinto mine. The applied statistical approach revealed that pH and electrical conductivity present a similar temporal evolution, which point to an identical geochemical signature; this indicates that both systems are similarly affected by contamination from the same pyritic area.